Implementation of the ASEAN Way in Resolving the Dispute Conflict between Thailand - Cambodia in 2011 - Utomo, Ananda Ramadhanti; Ahmadi, Sidiq (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
This research examines the implementation of ASEAN Way in conflict resolution between Thailand and Cambodia regarding the border dispute around the Preah Vihear Temple in 2011. ASEAN is faced with many problems related to disputes in its member countries, one of which is the problem of Thailand and Cambodia. The lack of clarity of the territorial line is one of the causes. Policies have been carried out, one of which is the 1962 International Court of Justice (ICJ) decision on the Preah Vihear Temple, which caused rejection from the Thai side due to different opinions regarding the layout of the country's territorial boundaries. The ASEAN Way, as a tool of regional diplomacy, will assist member states in mediating conflicts. They should rely on peaceful settlement of disputes, not interfere in the internal affairs of other ASEAN member states, and abandon the use of force. The ASEAN Way is considered "the superior product of cultural similarities among the people of ASEAN". The ASEAN way includes consensus-seeking activities and has formal and informal characteristics. Through the ASEAN Way mechanism with the track - one & track - two diplomacy approach method, it can be a success factor for ASEAN in resolving conflicts between the two disputing countries